Particularitățile comportamentului uman în natură și mediul social [Articol] - Cojocari, Lidia; Crivoi, Aurelia (CEP USM, 2016)
Human behavior a product of evolution and social development, a special form of interaction with the environment. So normal behavior – behavior that corresponds expected. In this case, the rule – is a set of social expectations about the behavior of people in a particular field.
Human behavior in natural and social enviroment
Keywords: behavior; level adjustment; necessity; adaptation